Influences of graphene on microbial community and antibiotic resistance genes in mouse gut as determined by high-throughput sequencing. (February 2016) - Xie, Yongchao; Wu, Bing; Zhang, Xu-Xiang; Yin, Jinbao; Mao, Liang; Hu, Maojie
Abstract: Graphene is a promising candidate as an antibacterial material owning to its bacterial toxicity. However, little information on influence of graphene on gut microbiota is available. In this study, mice were exposed to graphene for 4 weeks, and high-throughput sequencing was applied to characterize the changes in microbial community and antibiotic resistance genes (ARGs) in mouse gut. The results showed that graphene exposure increased biodiversity of gut microbiota, and changed their community. The 1 μg/d graphene exposure had higher influences on the gut microbiota than 10 μg/d and 100 μg/d graphene exposures, which might be due to higher aggregation of high-level graphene. The influence of graphene on gut microbiota might attribute to that graphene could induce oxidative stress and damage of cell membrane integrity. The results were verified by the increase of ratio of Gram-negative bacteria. Outer membrane of Gram-negative bacteria could reduce the membrane damage induced by graphene and make them more tolerance to graphene. Further, we found that graphene exposure significantly increased the abundance and types of ARGs, indicating a potential health risk of graphene. This study firstly provides new insight to the health effects of graphene on gut microbiota. Highlights: Graphene exposure increased the gut microbial diversity of mouse. 1 μg/d graphene had higher influence on gut micorbiota than 10 and 100 μg/d grapheme. Graphene increased abundances of oxidative stress and membrane-damage related genes. Gram-negative bacteria were more tolerant to graphene than Gram-positive bacteria. Graphene exposure increased types and abundances of antibiotic resistance genes.